Impact of economic value of ecotourism development on Income MSMEs: studies in Ternate, North Maluku - Prince Charles Heston Runtunuwu; Jay Rajasekera (Institute of Computer Science (IOCS), 2023)
The aims of this study are: (1) to determine the effect of attractiveness on income; (2) To determine the effect of ecotourism value on income; (3) To determine the influence of the attractiveness and value of ecotourism on income. The population in this study is all parts of the population, amounting to 100 people. Meanwhile, the number of research samples was 70 people. As for this study, the respondents were visitors and sellers at the Jikomalamo Beach tour. The test tool used is multiple linear regression analysis (multiple regression) using the statistical package for social scientists (SPSS) as a statistical test tool. From the research results show that; (1) partially positive and significant effect on income; (2) partially the value of ecotourism has a positive and significant effect on income; and (3) simultaneously shows that the attractiveness and value of ecotourism has a positive and significant effect on income.